Soil test crop response based fertilizer recommendations under integrated nutrient management for higher productivity of pearl millet (Pennisetum glaucum) and (Triticum aestivum) wheat under long term experiment - SHARMA, V K; PANDEY, R N; KUMAR, SARVENDRA; CHOBHE, KAPIL ATMARAM; CHANDRA, SURESH (The Indian Journal of Agricultural Sciences, 2016)
Field experiments were conducted to assess the soil test crop response (STCR) based fertilizer requirements for pearl millet-wheat sequence under integrated nutrient management (INM) under long term field experiment since 2003 at IARI, New Delhi. The results indicated that the STCR based fertilizer with 10 tonnes FYM/ha recorded highest mean grain (3.62 and 6.13 tonnes/ha) and stover/straw (7.0 and 8.01 tonnes/ha) yields of pearl millet (Pennisetum glaucum L. R. Br) and wheat (Triticum aestivum L.), which were 123.4 and 104.3 % higher in term of grain yield over control, respectively. STCR based fertilizer with 5 tonnes FYM/ha, STCR based chemical fertilizer and RDF treatments were statistically at par with respect to yield of pearl millet and wheat. Higher system grain yield (9.74 tonnes/ha) of pearl millet-wheat cropping system was recorded with STCR based integrated use of fertilizer with 10 tonnes FYM/ha. Nutrients uptake by pearl millet and wheat were significantly higher in STCR based fertilizer with 10 tonnes FYM/ha as compared to other treatments. Available N, P and K status in post-harvest soil was improved significantly with 20 tonnes FYM/ha alone as compared to other treatments but statistically at par with STCR based fertilizer with 10 tonnes FYM/ha. The long term study based on STCR clearly demonstrated that STCR based integrated use of fertilizer for targeting yield can produce targeted yield of crops and save the fertilizer without impairing soil fertility.